Comparative Genomic Analysis Revealed Distinct Molecular Components and Organization of CO2-Concentrating Mechanism in Thermophilic Cyanobacteria - Tang, Jie; Zhou, Huizhen; Yao, Dan; Riaz, Sadaf; You, Dawei; Klepacz-Smółka, Anna; Daroch, Maurycy (Frontiers in Microbiology, 2022)
Cyanobacteria evolved an inorganic carbon-concentrating mechanism (CCM) to perform effective oxygenic photosynthesis and prevent photorespiratory carbon losses. This process facilitates the acclimation of cyanobacteria to various habitats, particularly in CO2-limited environments. To date, there is limited information on the CCM of thermophilic cyanobacteria whose habitats limit the solubility of inorganic carbon. Here, genome-based approaches were used to identify the molecular components of CCM in 17 well-described thermophilic cyanobacteria. These cyanobacteria were from the genus Leptodesmis, Leptolyngbya, Leptothermofonsia, Thermoleptolyngbya, Thermostichus and Thermosynechococcus. All the strains belong to β-cyanobacteria based on their β-carboxysome shell proteins with 1B form of Rubisco. The diversity in the Ci uptake systems and carboxysome composition of these thermophiles were analysed based on their genomic information. For Ci uptake systems, two CO2 uptake systems (NDH-13 and NDH-14) and BicA for HCO3− transport were present in all the thermophilic cyanobacteria, while most strains did not have the Na+/ HCO3− Sbt symporter and HCO3− transporter BCT1 were absent in four strains. As for carboxysome, the β-carboxysomal shell protein, ccmK2, was absent only in Thermoleptolyngbya strains, whereas ccmK3/K4 were absent in all Thermostichus and Thermosynechococcus strains. Besides, all Thermostichus and Thermosynechococcus strains lacked carboxysomal β-CA, ccaA, the carbonic anhydrase activity of which may be replaced by ccmM proteins as indicated by comparative domain analysis. The genomic distribution of CCM-related genes was different among the thermophiles, suggesting probably distinct expression regulation. Overall, the comparative genomic analysis revealed distinct molecular components and organisation of CCM in thermophilic cyanobacteria. These findings provided insights into the CCM components of thermophilic cyanobacteria and fundamental knowledge for further research regarding photosynthetic improvement and biomass yield of thermophilic cyanobacteria with biotechnological potentials.